Advantages of Real Time Three‐Dimensional Echocardiography in the Assessment of Right Ventricular Volumes and Function in Patients with Pulmonary Hypertension Compared with Conventional Two‐Dimensional Echocardiography. Issue 7 (15th March 2013) - Di Bello, Vitantonio; Conte, Lorenzo; Delle Donne, Maria Grazia; Giannini, Cristina; Barletta, Valentina; Fabiani, Iacopo; Palagi, Caterina; Nardi, Carmela; Dini, Frank Lloyd; Marconi, Letizia; Paggiaro, Pierluigi; Palla, Antonio; et al.
<x xml:space="preserve">Abstract</x> Background In recent years, right ventricular (RV) function has acquired greater relevance as a clinical and prognostic marker in many physiopathological conditions. The study aims to point out the value of real time three‐dimensional echocardiography (RT3DE) and tissue Doppler imaging (TDI) in the evaluation of patients affected by pulmonary hypertension (PH), compared with conventional two‐dimensional (2D) echocardiography. Methods We enrolled 44 subjects affected by PH who underwent 2D and Doppler echocardiography, RT 3D Echocardiography and TDI evaluation of the RV, and a healthy control group. PH itself can induce severe functional and structural abnormalities of the RV, such as RV hypertrophy, RV dilation, and RV systolic and diastolic dysfunction. Results In this study, RV FAC, and TAPSE showed marked alterations in patients with PH compared to the control group (C): (RVFAC: [PH] 0.29 ± 0.07 vs. [C] 0.49 ± 0.05%, P < 0.0001; TAPSE: [PH] 15.3 ± 3.2 vs. [C] 21.1 ± 2.6 mm, P > 0.0001). The 3D RV end‐diastolic volume was significantly higher in PH than in C (PH) (138.7 ± 25.3 vs. [C] 82.8 ± 12.5 mL, P < 0.0001] as well as 3D RV end‐systolic volume (PH) (97.6 ± 21.5 vs. [C] 39.3 ± 9.5 mL, P < 0.0001). The 3D RV ejection fraction (EF) was significantly lower in the pulmonary hypertension group than in healthy subjects (31.8 ± 6.8 vs. [C] 52.5 ± 4.7%, P < 0.0001). Conclusions In patients with PH, evaluation of the RV diastolic and systolic volume and EF by RT3DE has shown a higher discriminating power in comparison, respectively, with 2DRV diastolic area and the relative fractional area changes.